Analisa penambahan unsur mangan pada remelting velg motor bekas terhadap nilai kekerasan - Rahmat Rudiansyah; Eko Nugroho; Asroni Asroni (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2022)
Remelting or metal casting is a recycling method that can be done to obtain a material with the desired physical and mechanical properties by changing its basic properties. Re-melting has a weakness, namely the toughness of the metal will decrease along with the re-melting treatment, due to phase changes that occur during the re-melting step, both physical and mechanical changes. Recycled aluminum wheels so that they can be reused properly and safely, treatment must be carried out to justify their structure. Manganese is used in several metal alloys to enhance favorable characteristics such as strength, hardness, and durability. The purpose of this study was to determine the hardness value of the effect of remelting used aluminum alloy wheels with manganese added in it. The research method used was experimental by re-melting used aluminum alloy wheels with manganese added, printing specimen models, and testing hardness using the Vickers method. The addition of manganese was carried out with a composition of 1.0%Wt, 1.2%Wt, and 1.4%Wt. The highest hardness value is owned by the specimen with the addition of 1.2%Wt manganese, which is 87.8 Kgf/mm2. The higher the Mn composition up to 1.2%Wt, the higher the hardness value. The hardness value will weaken when the addition of manganese exceeds 1.2%Wt.